2020
DOI: 10.3389/fnmol.2020.00087
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Cochlear Synapses by Systemic Administration of a Bisphosphonate

Abstract: Sensorineural hearing loss (SNHL) caused by noise exposure and attendant loss of glutamatergic synapses between cochlear spiral ganglion neurons (SGNs) and hair cells is the most common sensory deficit worldwide. We show here that systemic administration of a bisphosphonate to mice 24 h after synaptopathic noise exposure regenerated synapses between inner hair cells and SGNs and restored cochlear function. We further demonstrate that this effect is mediated by inhibition of the mevalonate pathway. These result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Because of the type 1C response, reversal of cochlear synaptopathy following noise has been a topic of intense research (Fernandez et al, 2021a;Hashimoto et al, 2019;Seist et al, 2020). A recently published study showed that treatment of mice with zoledronic acid after TTS-inducing noise can reverse synaptopathy, likely via the inhibition of the Farnesyl pyrophosphate synthase (FDPS) enzyme (Seist et al, 2020). Our study shows that expression of Fdps in the spiral ganglion is primarily limited to Schwann cells and type 2 SGNs, with a significant decrease in expression in Schwann cells following noise.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the type 1C response, reversal of cochlear synaptopathy following noise has been a topic of intense research (Fernandez et al, 2021a;Hashimoto et al, 2019;Seist et al, 2020). A recently published study showed that treatment of mice with zoledronic acid after TTS-inducing noise can reverse synaptopathy, likely via the inhibition of the Farnesyl pyrophosphate synthase (FDPS) enzyme (Seist et al, 2020). Our study shows that expression of Fdps in the spiral ganglion is primarily limited to Schwann cells and type 2 SGNs, with a significant decrease in expression in Schwann cells following noise.…”
Section: Discussionmentioning
confidence: 99%
“…The observed protection from synaptopathy may occur via prevention of the uncoupling of the paired IHC-ANF synapses, synaptic regeneration, or a combination of both phenomena. Recent studies demonstrate the potential for synaptic regeneration as treatment with bisphosphonates 24-h post-exposure can reverse synaptopathy [42]. Histological evaluation at additional post-exposure timepoints is needed to discriminate the two proposed mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…ABRs and DPOAEs were recorded as detailed previously ( Seist et al, 2020 ). Briefly, mice were anesthetized with intraperitoneally administered ketamine (100 mg/kg) and xylazine (10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%